PROTOTYPE OF AUTOMATIC TEMPERATURE MONITORING AND FEEDING SYSTEM FOR IOT-BASED MILKFISH CULTIVATION - Muhammad Ziadul Haikal; Atthariq; Muhammad Nasir (PT. Radja Intercontinental Publishing, 2024)
In the livestock industry, feeding work is usually carried out manually or using human power. Delays in feeding fish if farmers leave them for a long time can cause fish growth and endurance to decrease so that production results are unsatisfactory and harvests are delayed. Apart from delays in feeding, pond water temperature also has an important influence on fish growth. Cold or hot temperatures will affect fish production levels. In cultivating milkfish, fish growth conditions will be optimal if the temperature is 30℃ - 33℃. Unstable temperature changes can cause a decrease in water quality, even during the hatching process it can cause fish fry to die. Through this research, a tool was developed that can make the work of fish farmers easier. This tool is designed with a storage bucket as the main material and an Arduino Uno microcontroller circuit. Apart from that, this tool also uses a Thermocouple Temperature Sensor and uses 2 pump motors which function to drain and increase the flow of pond water, and this tool uses a servo motor which is used to control fish feed, this tool also uses an ESP8266 module to connect the network from smartphone to Arduino . The temperature monitoring output will be displayed on Android, users can normalize the water temperature by turning on the two pumps which aim to increase and decrease the water flow, so that the water temperature can be maintained.